Laporan Kasus Tinea Incognito : Penyalahgunaan Steroid - Yeremias Marturia Rocky Panggabean; Maria Manuella Sibarani; Glenessa Kuara; Raymond Davin Manik; Muhammad Andi Triputra (Pusat riset dan Inovasi Nasional, 2026)
Tinea incognito is a dermatophyte fungal infection when the clinical picture becomes unclear due to inappropriate treatment, which is usually caused by the use of topical steroids in cases of skin infections. A 46-year-old woman came with complaints of itchy reddish patches all over her body, experienced for 2 years. The itching worsened when consuming anchovies. The patient said she often took medication bought from a pharmacy without a doctor's prescription, the patient took methylprednisolone tablets and ointment. The itching complaint improved, but after stopping taking the medication, the itching complaint increased, and the patches widened. The patches first appeared on the right leg, initially resembling prickly heat spots then widened and spread to other parts of the body. Currently, the patches appear red in the shape of a ring with a clearer center. The patches were found on the face, neck, chest, abdomen, back, buttocks, left hand, and left foot. The patient noticed within a few months after taking the medication that her body was swollen, her weight increased, and her face looked rounder. A 20% KOH examination found hyphae and spores. Thus, the patient was diagnosed with Tinea Incognito caused by long-term topical steroid use. The patient was prescribed antifungal therapy with Ketoconazole 200 mg tablets once daily and Ketoconazole cream twice daily.